Ultra-small millimeter-wave filter chips based on high-K single-crystal lithium niobate - Qun Li; Junyan Zheng; Yansong Yang (Microsystems & Nanoengineering)
Abstract Next-generation communication systems require the mass deployment of ultra-small, high-performance filters that integrate multi-physical domains. However, achieving an optimal balance between miniaturization, low insertion loss, high selectivity, and low cost of millimeter-wave filters remains a challenge for existing technologies. Herein, we propose and demonstrate ultra-small millimeter-wave filters based on the multifunctional lithium niobate (LN) with outstanding nonlinear optical, electro-optic, piezoelectric, ferroelectric, and thermoelectric characteristics. As a high-K material with low dielectric loss and straightforward fabrication, LN provides an ideal platform for integrating photonic, acoustic, and electromagnetic functionalities. Notably, while LN is already proven for acoustic and optical signal processing, its potential for electromagnetic signal processing remains largely unexplored. In this work, we introduce second-order and fourth-order LN-based millimeter-wave bandpass filters (BPFs) tailored for narrowband and wideband millimeter-wave applications, respectively. Through careful optimization of the LN thickness, we elevate the cutoff frequencies of high-order modes, enhancing frequency selectivity while maintaining compactness. The LN-based BPFs exhibit record-breaking performance metrics, including minimal insertion loss, high selectivity, and compatibility with microfabrication processes. The LN-based BPFs fulfill the critical demands of millimeter-wave wireless communications, sensing, imaging, and emerging quantum information systems, paving the way for scalable, multi-physical integrated circuits.